2008
DOI: 10.1016/j.addr.2007.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors regulation of viral infection and disease☆

Abstract: In recent years, it has become increasingly evident that mammalian Toll-like receptors (TLRs) play a critical role in determining the outcome of virus infection. TLRs have evolved to recognize viral nucleic acids, and promote the stimulation of innate and adaptive immune responses. Interestingly, the study of mice harboring deficiencies in various TLR proteins and their adaptors suggests that TLR activation promotes protective anti-viral immunity in some cases, while exacerbating virusinduced disease in others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 118 publications
1
68
0
1
Order By: Relevance
“…It has been demonstrated that viral infections upregulate the expression of TLRs 33 34. TLR3, TLR7, TLR8 and TLR9 typically reside in the endosomes where they can gain access to viral nucleic acids 35. TLR7 recognises ssRNA in the cytoplasm of infected cells during viral replication 36.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that viral infections upregulate the expression of TLRs 33 34. TLR3, TLR7, TLR8 and TLR9 typically reside in the endosomes where they can gain access to viral nucleic acids 35. TLR7 recognises ssRNA in the cytoplasm of infected cells during viral replication 36.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, TLR7 senses a specific invariant feature present in the genomic RNA or viral replication intermediates of these viruses. However, little evidence exists regarding the particular viral ligand that serves as the authentic pathogen‑associated molecular pattern that binds to TLR7, or about the regulation of TLRs by viruses 35 37. It is also possible that microorganisms different from viruses or an endogenous TLR7 stimulus of non-infectious origin may induce a type I IFN response through the TLR7 pathway 3841.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor κB (NF-κB), interferon (IFN) regulatory factor (IRF)-3, IRF-5, and IRF-7 are the factors which mediate these responses. [32] NF-κB mediate the inflammatory response to HCV by inducing chemokines and proinflammatory cytokines in parallel with tumor necrosis factor-α (TNF-α).…”
Section: Innate Immunitymentioning
confidence: 99%
“…Pathogen-associated molecular patterns (PAMPs) are detected by pattern recognition receptors (PRRs), such as Toll-like receptors (TLRs) [5]. Viral infections are mainly detected by the endosomal TLRs that are activated by nucleic acids, including TLR3, TLR7, TLR8 and TLR9.…”
Section: Innate Immune Response In Viral Myocarditismentioning
confidence: 99%